Rhetoric and reality: Critique of the Commission's approach to EPAs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Two southern African MPs have launched a booklet entitled 'Beyond the Rhetoric...